The Influence of Reading Corner Utilization on Students' Literacy Skill: An Experimental Study at Elementary School - Lutfiyyah Ningtyas; Rintis Rizkia Pangestika; Nur Ngazizah (JIP Jurnal Ilmiah PGMI, 2024)
This study aims to analyze the effect of the use of reading corners on the literacy skills of elementary school students. This study uses a quantitative research method Pre-Experimental Design with the type of One-Group Pretest-Postest Design. The subjects of this study were all fifth grade students of Bajangrejo State Elementary School, totaling 12 students. The data collection technique was in the form of a test. The sample used was the total sample. The data analysis used was in the form of descriptive statistics, normality tests, homogeneity tests and parametric statistical hypothesis tests. in paired form sample t- test using SPSS 26. The results of this study obtained an average pretest value of 43.33 and a posttest of 71.25. Based on the results of the hypothesis test using Paired Sample T- Test obtained information that the calculated t value obtained -5.786 > t table 2.20099 and the significance value in the Sig column. (2-tailed) 0.000 which means 0.000 < 0.05, then it can be concluded that H1 is accepted and H0 is rejected. This study shows that the use of reading corners has a positive and significant influence on the literacy skills in Elementary School.